Nation and history : Polish historians from the Enlightenment to the Second World War - Brock, Peter, 1920-2006; Stanley, John, 1949-; Wróbel, Piotr (Heritage, 2006)
While featuring different approaches, Nation and History serves as the most comprehensive work on Polish historiography written in English.